2020
DOI: 10.1039/d0fo00567c
|View full text |Cite
|
Sign up to set email alerts
|

A study on the protective effects of taxifolin on human umbilical vein endothelial cells and THP-1 cells damaged by hexavalent chromium: a probable mechanism for preventing cardiovascular disease induced by heavy metals

Abstract: Taxifolin suppressed the toxicity and THP-1 cell adhesion to HUVECs induced by Cr(vi) via regulating the p38 MAPK and JNK pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Son et al have also reported that Cr(VI) treatment could induce JB6 murine epidermal cells apoptosis by up‐regulation of JNK signaling 36 . Similarly, Cao et al have also showed that Cr(VI) exposure could increase the phosphorylation of p38 and JNK, which regulated the expression of Bax and Bcl‐2 in human umbilical vein endothelial cells 37 . Taken together, these studies well support the results of our experiment, that is, ROS induced by Cr(VI) promotes the activation of JNK pathway.…”
Section: Discussionmentioning
confidence: 92%
“…Son et al have also reported that Cr(VI) treatment could induce JB6 murine epidermal cells apoptosis by up‐regulation of JNK signaling 36 . Similarly, Cao et al have also showed that Cr(VI) exposure could increase the phosphorylation of p38 and JNK, which regulated the expression of Bax and Bcl‐2 in human umbilical vein endothelial cells 37 . Taken together, these studies well support the results of our experiment, that is, ROS induced by Cr(VI) promotes the activation of JNK pathway.…”
Section: Discussionmentioning
confidence: 92%
“…On the one hand, SREBP-1 plays and progression of HCC and is an ideal intervention target for HCC treatment. Small molecule inhibitors are an ideal mode of action for specific targets (71)(72)(73)(74). The existing SREBP-1 small molecule inhibitors are mainly Betulin, Pseudoprotodioscin and Fatostatin (75)(76)(77).…”
Section: Discussionmentioning
confidence: 99%
“…There is much evidence showing that the major inflammatory cytokines during this process are the IL-1 family ( Carty et al, 2009 ; Herder et al, 2017 ; Pfeiler et al, 2019 ), IL-6 ( Carty et al, 2009 ; Prochnau et al, 2012 ; Morieri et al, 2017 ), IL-17 ( Madsen et al, 2016 ), IL-18 ( Buraczynska et al, 2016 ; Lee et al, 2019 ), IL-32 ( Damen et al, 2017 ), TNF-α ( Singh et al, 2005 ; Shen et al, 2016 ), C-reactive protein (CRP) ( Chiang et al, 2019 ; Martin-Nunez et al, 2020 ). Adhesion Molecules are also very important, such as vascular cell adhesion molecule-1 (VCAM-1) ( Denys et al, 2016 ; Kunutsor et al, 2017 ; Cao et al, 2020 ; Yari et al, 2020 ), intercellular adhesion molecule-1 (ICAM-1) ( Cao et al, 2020 ; Yari et al, 2020 ), and platelet endothelial cell adhesion molecule-1 (PECAM-1) ( Stevens et al, 2008 ). SGLT-2 inhibitors are recognized as effective agents for decreasing these inflammatory factors.…”
Section: Sglt-2 Inhibitors Improve Diabetic Cardiovascular Diseases B...mentioning
confidence: 99%